2012
DOI: 10.1111/btp.12013
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Seedling Assemblages in a Fragmented Tropical Landscape: Implications for Forest Regeneration

Abstract: Whether aging forest fragments are able to recover original assemblages or progressively move toward impoverished successional stages remains as an open question. This study tested the hypothesis that seedling assemblages in forest fragments differ from those across mature forest stands and examined to what extent the uncovered patterns supported the notion that edge‐affected habitats tend to support impoverished tree assemblages dominated by pioneer species. We contrasted a series of small forest remnants (3–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
3
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 59 publications
8
51
3
4
Order By: Relevance
“…Pütz et al 2011;Tabarelli et al 2008), (4) some native pioneer species are proliferating at multiple spatial scales , particularly Byrsonima sericea, Bowdichia virgilioides, Cupania oblongifolia and Cupania racemosa. Although it has been shown that tree assemblages in small forest fragments are predominantly comprised of small-seeded species (Melo et al 2010;Santo-Silva et al 2013;Santos et al 2008), our results suggest that production of large numbers of small seeds in itself does not necessarily confer the ability to proliferate in small fragments.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…Pütz et al 2011;Tabarelli et al 2008), (4) some native pioneer species are proliferating at multiple spatial scales , particularly Byrsonima sericea, Bowdichia virgilioides, Cupania oblongifolia and Cupania racemosa. Although it has been shown that tree assemblages in small forest fragments are predominantly comprised of small-seeded species (Melo et al 2010;Santo-Silva et al 2013;Santos et al 2008), our results suggest that production of large numbers of small seeds in itself does not necessarily confer the ability to proliferate in small fragments.…”
Section: Discussioncontrasting
confidence: 80%
“…In particular (1) population declines and local extinctions in human-modified landscapes predominantly affect particular functional groups (XXXX), (2) edge-affected habitats tend to support distorted tree species assemblages in both taxonomic and functional terms (Laurance et al 2006a;Laurance et al 2006b;Tabarelli et al 2008), (3) these distortions can be readily observed in seedling assemblages (Santo-Silva et al 2013); (3) small forest fragments are becoming increasingly dominated by pioneer species (cf. Pütz et al 2011;Tabarelli et al 2008), (4) some native pioneer species are proliferating at multiple spatial scales , particularly Byrsonima sericea, Bowdichia virgilioides, Cupania oblongifolia and Cupania racemosa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations